AN INVESTIGATION INTO LINGUISTIC FEATURES OF VERBS DENOTING NEGATIVE “VERBAL ACTION” (ENGLISH VS. VIETNAMESE) - Assoc. Prof. Dr. PHAN VĂN HÒA (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
There are many ways of studying verbal processes. However, this thesis is restricted to the study of verbs denoting NAV in process of saying such as murmur, sob, shout, curse, mutter, scold, thunder, complain, grumble, scream, sob……. and their counterparts in Vietnamese such as la hét, chửi mắng, chửi rủa, càu nhàu, lầm bầm, làu bàu, gầm thét, xì xào, nạt, nạt nộ, rầy, rầy la, cằn nhằn, xỉ vả, mắng, nhiếc, nhiếc móc, nhiếc mắng…..They are examined in accordance with syntactic, semantic and pragmatic aspects. And these are explored in Vietnamese and English texts, novels and short stories.